Regional Redistribution Effects of Renewable Energy Subsidies - Sapio, Alessandro (Journal of Environmental Accounting and Management, 2026)
Through a theoretical model of subsidies for renewable energy (RE), the paper shows that regions characterised by high energy demand and low RE endowments contribute disproportionately to the green energy budget. Such a pattern is emphasised if subsidies are tied to wholesale electricity prices, because the merit order effect associated with renewables, by depressing the electricity price, justifies higher subsidies to RE generators. Due to a pecuniary externality, interconnection between regions allows the region with a lower income and richer RE production to partly shift the burden of RE support on the other region. These spatial patterns can be overturned if RE ownership is distributed across zones, and under some parameter sets in which market integration implies a heavier unit burden of RE support.